Wounded river : the Civil War letters of John Vance Lauderdale, M.D. - Lauderdale, John Vance (Michigan State University Press, 1993)
The Wounded River takes the reader back more than 130 years to reveal a marvelous, first-hand account of nineteenth-century warfare. In the process, the work cuts the legends and mythology that have come to frame and define accounts of America's bloodiest war. Of equal significance, Peter Josyph's editorial work on this superb collection of letters from the Western Americana Division of Yale University's Beinecke Rare Book and Manuscripts Library enhances and clarifies Lauderdale's experinces as a surgeon aboard the U.S. Army hospital ship D.A. January.